Quantitative estimation of serum 25(OH) D and associated risk factors of vitamin D deficiency among pregnant women attending a tertiary care hospital in Udaipur, Rajasthan - Akanksha Bhatnagar; Kusum Mittal; Jitendra Kumar Meena; Pooja Gandhi; Neelesh Bhatnagar (Al Ameen Medical College, 2022)
Introduction: Insufficiency of vitamin D is now known globally and is exceptionally common in temperate and tropical countries. Due to its several negative maternal and fetal health consequences, vitamin D insufficiency in pregnancy is a growing concern worldwide. Methods: A cross-sectional study was conducted at a tertiary medical hospital for one year. A sample of 280 pregnant women attending antenatal clinic (ANC) were enrolled using a random sampling technique. A standard questionnaire was designed to collect socio-demographic details and the sun exposure of participants. To analyse dietary habits and consumption of vitamin D-rich foods, a food frequency questionnaire (FFQ) was used. Serum samples were obtained and analyzed for and calcium levels. Results: High prevalence of maternal vitamin D insufficiency 122 (43.57%) and deficiency 92 (32.85%) observed. Most 263 (94%) participants had adequate serum calcium levels (> 8.5 mg/dL). Younger participants (< 25 yrs.) had low mean vitamin D (17.61±13.89 ng/mL), adequate calcium (9.52±0.70 mg/dL) levels. Rural residence, multigravida, advanced trimester, poor education, joint family, unemployment, and lower socioeconomic status were found associated with vitamin D insufficiency. Conclusion: In the present study a high prevalence of maternal vitamin D deficiency was observed. The burden of Vitamin D inadequacy (76.39%) reflects poor nutritional status and health risks for mothers and fetuses. Sociodemographic factors (Residence, Education, Family, and Socioeconomic status) were linked to this micronutrient deficiency. There is a need for further community-based nutritional research on sociodemographic, biological, and nutritional determinants for in-depth understanding.